The Infragluteal Sulcus: A Histologic and Ultrasonographic Study - ERGÜN, SELMA; ERGÜN, SELMA; Gayretli, Ozcan; Kilicarslan, Rukiye; Bilgic, Bilge (My University, 2013)
The buttocks are a major component of sexual attraction, and they have their place in the concept of beauty in most cultures and ethnic groups. The infragluteal sulcus, an important part of the gluteal region, determines the attractiveness of the buttocks. For that reason, any small change in the infragluteal sulcus makes a major cosmetic difference in the morphology of the buttock. In recent years, some flaps such as the infragluteal flap, the transverse upper gracilis flap, and the transverse musculocutaneous gracilis flap have become popular because of reduced donor area morbidity and their availability for hiding incision scars. In these cases, there may be distortion of the gluteal morphology and infragluteal sulcus. In this study, the anatomic and histologic features of the tissues that form the infragluteal sulcus were analyzed for their contribution to successful reconstruction of the infragluteal sulcus.